Effective practices of state support for social entrepreneurship in the global economy - Spanova, B.K.; Magda, R. (BUKETOV BUSINESS REVIEW, 2018)
The article examines the issue of regulating social entrepreneurship in OECD countries as one of the leading actors in the public sector that provides social services to the population. The authors analyze the evolution of organizational forms of social entrepreneurship, taking into account the historically developed features of institutional development in different regions of the world. Against the backdrop of evolutionary processes, the authors consider the regulatory and legal framework for regulating social entrepreneurship in the aggregate of its limitations and methods of supporting the activities of such organizations. It is revealed that in the development of social entrepreneurship of a group of developed countries, the world has three main stages. Proceeding from this, the legalization of the activities of social entrepreneurship went in two ways: adapting the cooperative form of economic activity and highlighting the legal norms of activity. The analysis and assessment of the regulatory framework for the regulation of social entrepreneurship in the developed countries of the world made it possible to identify the characteristics of its legal personality, the differences between countries in the methods of regulation and the norms and instruments used, which would enable Kazakhstan to choose the most effective norms and create favorable conditions for the development of this phenomenon. The assessment given by the authors of the general and special in stimulating this sector in the context of a postindustrial economy is of value from the point of view of designing institutional support for social entrepreneurship in Kazakhstan.